2021
DOI: 10.21608/ejchem.2021.65939.3417
|View full text |Cite
|
Sign up to set email alerts
|

Camel (Camelus Dromedarius) Milk Antibodies Ameliorated Diethylnitrosamine-Induced Hepatocellular Carcinoma in Wistar Rats

Abstract: Hepatocellular carcinoma (HCC) is an extremely aggressive solid tumor and relates to numerous cases of cancer-associated deaths globally. Current studies reveal that natural compounds retain various therapeutic effects. This study was aimed to investigate the beneficial antitumor effects of camel (Camelus dromedarius) milk antibodies (CM-IgG) on diethylnitrosamine (DENA)-induced hepatocellular carcinoma in male Wistar rats. Hepatocarcinoma was induced in rats using DENA (50 mg/kg, twice/week) for 2 weeks follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Moreover, IgG camel milk significantly alleviated hepatocellular morphology alterations and down-regulated GST-P gene expression levels in the liver. The study concluded that there is an improvement in the dysfunction of the liver induced by DENA as well as in the oxidative stress in the rats having hepatocarcinoma was all attributed to the immunoglobulins purified from camel milk ( 46 ). Figure 2 explains the effect of camel milk on liver carcinoma.…”
Section: Hepatoprotective Effect Of Camel Milkmentioning
confidence: 99%
“…Moreover, IgG camel milk significantly alleviated hepatocellular morphology alterations and down-regulated GST-P gene expression levels in the liver. The study concluded that there is an improvement in the dysfunction of the liver induced by DENA as well as in the oxidative stress in the rats having hepatocarcinoma was all attributed to the immunoglobulins purified from camel milk ( 46 ). Figure 2 explains the effect of camel milk on liver carcinoma.…”
Section: Hepatoprotective Effect Of Camel Milkmentioning
confidence: 99%